Flouting the Cooperative Principle in BoJack Horseman A Reflection of the Main Character - Ni Made Yulia Sari; I Gusti Ayu Agung Sintha Satwika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates how conversational maxims are flouted by the main character in Episode 1 of Season 1 of the adult animated series BoJack Horseman, and how such flouting contributes to character development and narrative function. Grounded in Grice’s Cooperative Principle, the analysis adopts qualitative content analysis supported by frequency counts to identify types and strategies of maxim flouting. The findings show that BoJack most frequently flouts the maxims of Relation and Quality through topic shifting, sarcasm, and hyperbole. These strategies function pragmatically to avoid accountability, express self-defense and denial, and generate humor while advancing the narrative. By linking maxim flouting to character psychology rather than merely describing occurrences, the study contributes to pragmatic analysis of characterization in adult animated series.